DEVELOPING MUSICAL LITERACY THROUGH BRAILLE MUSIC NOTATION (The Conference Hub, 2026)
This scientific article examines the methodology of developing musical literacy through Braille music notation in the context of visually impaired learners, approaching the issue not as a technical adaptation but as a complex pedagogical and cognitive process. Conducted within the IMRaD framework, the study explores Braille music notation as a tactile–semantic system that restructures musical cognition, auditory perception, and symbolic thinking in the absence of visual input. The article argues that musical literacy for visually impaired students cannot be achieved through the direct transfer of visually oriented pedagogical models, but requires a methodologically grounded approach based on sensory compensation, cognitive load management, and reflective musical processing. Particular attention is given to the role of Braille notation in fostering analytical listening, internal musical representation, and independent score reading. The findings highlight that Braille music literacy becomes pedagogically effective only when integrated into a carefully structured methodological system that prioritizes musical meaning over mechanical decoding. The study provides a methodological foundation for inclusive music education practices and contributes to the broader discourse on accessibility and equity in music pedagogy.